Tobacco Consumption among High School Adolescents - Upreti, Yadu Ram (Journal of Health Promotion, 2018)
This article highlights the practice of tobacco consumption among high school adolescents of Hariwan municipality, a growing semi-urban area of Sarlahi district in Nepal. The study utilized descriptive cross-sectional survey research design with quantitative method to get the required information to the study. Four high schools (two community and two private schools) were randomly sampled to select the respondents. In total, 224 adolescents (n=224) aged 15 to 19 years studying in grade eleven and twelve were selected. A set of pretested self-administered questionnaire was employed to collect the required information. Before data were collected, verbal consent was obtained from the authority of schools and respondents themselves. Only self-reported primary nature of data were utilized to obtain answers to the research questions. Data were entered and analyzed using SPSS software with 16.0 versions. Chi-square test and t-test of bivariate analysis were used to analyze the results. The study revealed that around one-fourth (22.8 %) of high school adolescents consumed at least one type of tobacco products. Cigarette was the most common tobacco product among the youth followed by Panparag and Gutkha. Most of them consumed tobacco for entertainment followed by experimentation. Various factors are associated with the consumption of tobacco amongst which peer pressure, parental and relatives’ influence, and media exposure remain significant ones. Monitoring high-risk behaviors, announcing tobacco-free public places, making aware towards glamorized tobacco promotional pro-active advertisements, etc. will be effective to minimize the tobacco consumption practice among in-school youths. Journal of Health Promotion Vol.6 2008, p.86-91